41. Dose intercomparison at European hadrotherapy centers. (December 2018) - Guida, F.; Barbato, A.; Di Lillo, F.; Mettivier, G.; Ciocca, M.; Mastella, E.; Liotta, M.; Tarabelli De Fatis, P.; Schwarz, M.; Lorentini, S.; Cirrone, P.; Petringa, G.; et al.
Abstract : Purpose: To perform the first intercomparison study on nominal doses delivered by the Treatment Planning System in various European hadrontherapy centers, using an ionization chamber for reference dosimetry in water, according to IAEA TRS398 code of practice. Methods: Measurement sites include the following clinical therapy centers: CNAO (Pavia) and HIT (Heidelberg) for protons and carbon ions; TPC - (Trento) and CATANA (Catania) for protons; Fondazione Maugeri (Pavia) for 6 MV photons. For ion beams, both single monoenergetic layer and SOBP, have been delivered to obtain a nominal dose of 2 Gy at the reference depth zref = 2 cm in a water phantom. The energies used were: in CNAO for protons (118.19 MeV, 173.61 MeV) and for carbon ions (208.58 MeV/u, 332.15 MeV/u), in Fondazione Maugeri 6 MV and in TPC - for protons (118 MeV, 173 MeV)[1] . Measurements were made with a PTW Farmer 30010-1 ionization chamber. Results: CNAO, Fondazione Maugeri and TPS data show consistency within the experimental uncertainties, with a maximum relative deviation of 2.8%. The full set of measurements is planned to be completed in 2018. Conclusions: Absorbed dose for clinical proton beams (118.19 MeV and 173.61 MeV) is consistent within less than 3% between CNAO and TPS, as well as for 6 MV photons. This work was performed within INFN projects RDH and MC-INFN.